Comparative Study of Phytochemicals and Proximate Composition of Parkia biglobosa, Xylopia aethiopica and Aframomum melegueta for Nutraceutical Applications - Audu, H.; Ajibade, G. A.; Dibal, D. M.; Magaji, Y. (Sahel Journal of Life Sciences FUDMA, 2025)
This study was conducted to compare the phytochemical constituents, proximate composition, and concentration of Vitamin C, E, and B carotene of Aframomum melegueta, Xylopia aethiopica, and Parkia biglobosa to determine which spice has the highest antioxidant potential. The methanol extracts of the spice plants were subjected to Phytochemical, Proximate, and Vitamin Screening using Standard Procedures. The results showed that all three selected spices contained tannins, saponins, flavonoids, steroids, and cyanogenic glycosides in varying levels of abundance but differed in the presence of alkaloids. Parkia biglobosa contained the highest concentration of Flavonoids (136.74±0.015), Xylopia aethiopica contained the highest concentration of Vitamin E (10.30mg/100g and Beta Carotene (11.08mg/100g) which are good sources of antioxidants. Aframomum melegueta contained the highest amount of vitamin C (19.10±0.02). Parkia biglobosa extract was richest in protein with 35.02% and fat (25.57%) while Xylopia aethiopica was found to have a high amount of carbohydrates (63.15%) and the lowest amount of lipid (10.27%) and protein (8.75%). The result showed that the inclusion of these spices in food is highly recommended and even more in a combined form as synergetic functionality will provide the body with the required nutrients and antioxidants for disease prevention as well as the maintenance of good health.